2021
DOI: 10.1042/cs20201283
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the expression and functional activities of Myosin II isoforms in human hyperplastic prostate

Abstract: Benign prostatic hyperplasia (BPH) is a common disease among aging males with the etiology remaining unclear. We recently found myosin II was abundantly expressed in rat and cultured human prostate cells with permissive roles in the dynamic and static components. The present study aimed to explore the expression and functional activities of myosin II isoforms including smooth muscle (SM) myosin II (SMM II) and non-muscle myosin II (NMM II) in the hyperplastic prostate. Human prostate cell lines and tissues fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 59 publications
3
5
0
Order By: Relevance
“…In addition, RhoA knockdown resulted in down-regulated expression of cytoskeletal components NMMHC-A and NMMHC-B. Previous studies had shown that NMMHC-A and NMMHC-B could promote proliferation and inhibit apoptosis of prostate cell lines (He et al 2021 ), their downregulation was therefore consistent with the observed proliferation and apoptosis trends.…”
Section: Discussionsupporting
confidence: 78%
“…In addition, RhoA knockdown resulted in down-regulated expression of cytoskeletal components NMMHC-A and NMMHC-B. Previous studies had shown that NMMHC-A and NMMHC-B could promote proliferation and inhibit apoptosis of prostate cell lines (He et al 2021 ), their downregulation was therefore consistent with the observed proliferation and apoptosis trends.…”
Section: Discussionsupporting
confidence: 78%
“…As previously reported [12,16,18], the differences in nucleic acid sequence in each pair of SMM isoforms were quite small. Because of this, competitive RT-PCR was used to detect the expression of SMM isoforms.…”
Section: Competitive Rt-pcrsupporting
confidence: 74%
“…Previously, we collected human hyperplastic prostate tissues from 10 patients undergoing radical cystectomy and found that hyperplasia prostate SM expressed more MHC, NMMHC-A, and NMMHC-B when compared to normal prostate tissues [16]. In this study, as shown in Figure 1, the inclusion criteria were extended, and we included 30 BPH patients who sought surgical treatment for moderate-to-severe LUTSs secondary to BPO or acute/chronic urine retention.…”
Section: Introductionmentioning
confidence: 99%
“…Cell lines obtained and cultured, CCK-8 assay, total RNA extraction, RNA reverse transcription, qRT-PCR analysis, Western blot analysis, hematoxylin and eosin (H&E) staining and masson’s trichrome staining analysis were performed as we previously described [ 35 , 36 ]. Primer sequences were summarized in Additional file 1 : Table S1.…”
Section: Methodsmentioning
confidence: 99%